Changes on the national labor market during the pandemic period (Economic and Political Thought, 2022)
The aim of the article is to examine changes in the domestic labor market during the pandemic. It is mainly about analyzing and assessing the changes that take place during the pandemic compared to the previous year as well as the previous period. To examine the changes, the following data will be used: average employment in the enterprise sector (economic entities employing more than 9 people), registered unemployment (as at the end of the period), registered unemployment rate (as at the end of the period), average monthly nominal gross salary in the sector enterprises and the average monthly real gross salary in the enterprise sector. Monthly data for 2020 and 2021 will be used for the analysis and evaluation. Based on these data, a statistical analysis will be carried out using the dynamics of changes. The dynamics will be performed in two ways: the analogous period of the previous year = 100, the previous period = 100. The data used is published on the website of the Central Statistical Office in Warsaw.
Keywords: labor market, employment, unemployment, salaries